The combination of sucrose dilaurate and sucrose laurate suppresses HMGB1: an enhancer of melanocyte dendricity and melanosome transfer to keratinocytes. (11th January 2022) - Wang, J.; Jarrold, B.; Zhao, W.; Deng, G.; Moulton, L.; Laughlin, T.; Hakozaki, T.
Abstract: Background: Hyperpigmented spots are common issues in all ethnicities, involving multiple intrinsic and extrinsic factors such as UVB exposure, hormone balance, inflammatory status and ageing. Objectives: To determine (i) melanocyte dendricity in multiple facial spot types, (ii) impact of High Mobility Group Box 1 (HMGB1), and the combination of sucrose dilaurate and sucrose laurate (SDL) on melanogenesis and melanocyte dendricity, and (iii) SDL effect on facial spots in a human use test. Methods: Facial spot and adjacent non‐spot skin biopsies were collected from Chinese women (age 20‐70). Histological assessment of melanocyte dendricity was performed for 3 spot types (solar lentigo, melasma and postinflammatory hyperpigmentation) by immunofluorescent staining for c‐kit/MITF. Keratinocyte, melanocyte and melanocyte–keratinocyte co‐culture models were used to assess HMGB1 release by UVB radiation, the effects of HMGB1 and SDL on melanin production, melanocyte dendricity and melanosome transfer. The effect of an SDL‐containing moisturizer on appearance of facial hyperpigmented spots was assessed against a vehicle control in an 8‐week human use test. Results: Melanocytes in spot areas are more dendritic than melanocytes in adjacent non‐spot skin across three investigated spot types. In cell culture models, a moderate UVB‐radiation exposure caused release of HMGB1 from keratinocytes. HMGB1 did not alter melanin production in melanocytes, but enhanced melanocyte dendricity and melanosome transfer. SDL reduced HMGB1 release from keratinocytes, inhibited melanin production, reversibly suppressed melanocyte dendricity and reduced melanosome transfer. In the human use test, SDL‐containing moisturizer reduced appearance of spots versus vehicle. Conclusion: Increased melanocyte dendricity was observed in multiple types of facial spots. Addition of HMGB1 protein increased melanocyte dendricity and melanosome transfer in cell cultures, implicating potential involvement in spot formation. SDL suppressed melanin production, melanocyte dendricity and melanosome transfer in vitro and reduced appearance of spots in the use test, suggesting SDL is an effective solution to address hyperpigmented spot concerns.